Dari Regulasi ke Realita Sosial: Evaluasi Kebijakan Anti Kekerasan di Kampus - Ikhlasiah Dalimoenthe; Rusfadia Saktiyanti Jahja; Ahmad Rifqy Ashshiddiqy (Prophetic : Professional, Empathy, Islamic Counseling Journal, 2025)
This research examines the effectiveness of the University Violence Handling Task Force in controlling the problem of violence on Campus. The previous study concluded that there were many incidents of violence that were not revealed on campus due to the constraints of power relations and social pressure experienced by the victims. This view contains weaknesses as if the campus does not have good governance in dealing with violent events and tends to ignore it because it concerns the authorities. The argumentation of this article shows that the PPK Task Force is institutionally quite well known and plays a role in dealing with the problem of violence on campus. If there is a victim who is reluctant to complain, the problem is more caused by psychological problems. For that, it is necessary to strengthen and empower victims, as well as improve governance in socialization about the role of the Task Force. Thus, in the future, the work of the PPK Task Force will be more effective. This research uses a mixed approach by combining online survey methods and in-depth interviews.